AN EXTENSIVE REVIEW ON MEDICINAL PLANTS IN THE SPECIAL CONTEXT OF ECONOMIC IMPORTANCE - NATH, RAJAT; KITYANIA, SIBASHISH; NATH, DEEPA; TALKUDAR, ANUPAM DAS; SARMA, GADAPANI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Our health-care system would be incomplete without the use of medicinal herbs. In the days before modern medicine, several communities created medical knowledge systems known as “traditional medicine,” “indigenous medicine,” or “folk medicine.” The medicinal properties of plants and plant-based products are widely accepted. There are a variety of medical approaches available across the world, including allopathic, homoeopathic, Ayurvedic, and Chinese. The developed communities each have their own Materia Medica, which compiles thorough data on many plants used as medicines. According to current estimations from the field of botany, there are somewhere between 2,50,000 and 3,50,000 distinct plant species in existence. It is estimated that 35,000 unique species are used to cure a wide range of ailments in diverse places throughout the world. Based on general popularity among all ages, phytopharmaceuticals are an integral part of worldwide business and the global economy. According to a globe news wire study, the global herbal medicine market is estimated to be 550 billion dollars by 2030, up from 83 billion dollars in 2019. China and India lead the global herb market. China exports 120,000 tonnes of herbal remedies annually, followed by India with 32,000 tonnes. Europe is the world’s largest importer of medicinal plants (MP), taking in over 400,000 tonnes annually to fulfill local demand. In this review, we have discussed about the MP and their economic importance in global market.